ANALISIS DAN PERANCANGAN DASHBOARD DATA KARYAWAN PADA PT SOLEN SYSTEM INDONESIA DI YOGYAKARTA - Rut Febrianty; Restyandito; Lukas Chrisantyo (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2023)
PT Solen System Indonesia is a company engaged in the manufacture of software. PT Solen System Indonesia has employee data containing sprint review data. Sprint review data is data per week that is inputted into the google sheets file. With the data number reaches from 24 google sheet files over a period of one year, admins have difficulty because they have to access google sheets files one by one to be able to view employee performance data. Admin cannot know the extent of the performance of each employee in completing the workload in a certain period. Thus, a website-based strategic dashboard was created using the User centered Design (UCD) method. The dashboard was then tested using usability test and SUS. Results of the dashboard test for the admin and all employees of PT Solen System Indonesia obtained an effectiveness value of 89%, efficiency of 78% and satisfaction of 85%.